2009
DOI: 10.1111/j.1468-2478.2008.01523.x
|View full text |Cite
|
Sign up to set email alerts
|

Sleeping With Your Friends’ Enemies: An Explanation of Sanctions-Busting Trade

Abstract: Research indicates that if third parties provide assistance to sanctioned states, the sanctions are less likely to be successful. However, the scholarship on the profile of sanctions busters and their motivations remains underdeveloped. Drawing on the realist and liberal paradigms, this piece develops two competing theories to account for third-party sanctions-busting. The hypotheses drawn from these theories build upon existing work on sanctions, the political determinants of international trade, and the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
91
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(95 citation statements)
references
References 35 publications
3
91
0
1
Order By: Relevance
“…5 The role of sanctions buster or ''black knight'' countries that come to the aid of the target (Early, 2009), and the difficulties involved in establishing and maintaining a sanctions coalition (Drezner, 2000;Kaempfter and Lowenberg, 1999;Mansfield, 1995;Martin, 1992;Miers and Morgan, 2002), are frequent topics in the sanctions literature. Hufbauer et al (2007) maintain that one reason why sanctions may fail is that powerful or wealthy allies of the target come to its aid.…”
Section: Fdi and The Effectiveness Of Us Sanctionsmentioning
confidence: 99%
“…5 The role of sanctions buster or ''black knight'' countries that come to the aid of the target (Early, 2009), and the difficulties involved in establishing and maintaining a sanctions coalition (Drezner, 2000;Kaempfter and Lowenberg, 1999;Mansfield, 1995;Martin, 1992;Miers and Morgan, 2002), are frequent topics in the sanctions literature. Hufbauer et al (2007) maintain that one reason why sanctions may fail is that powerful or wealthy allies of the target come to its aid.…”
Section: Fdi and The Effectiveness Of Us Sanctionsmentioning
confidence: 99%
“…Sanctions busters are states that dramatically increase their trade and/or foreign assistance with target states after they have been sanctioned (Hufbauer et al 2007;Early 2009Early , 2011. Sanctions busters are states that dramatically increase their trade and/or foreign assistance with target states after they have been sanctioned (Hufbauer et al 2007;Early 2009Early , 2011.…”
Section: Economic Sanctions Spoiler Behaviors and International Insmentioning
confidence: 99%
“…Early (2009Early ( , 2012 has shown that most of the sanctions-busting trade conducted by third-party states is driven by commercially motivated firms and traders. Commercial motivations are at the heart of what drives most private actors to engage in sanctions-busting trade, whereas government interests in sanctionsbusting are shaped by both the commercial and political benefits it can provide.…”
Section: Economic Sanctions Spoiler Behaviors and International Insmentioning
confidence: 99%
See 2 more Smart Citations